VERIFICATION AND VALIDATION OF STUDENT’S CFD TOOL ON THE VENTURI FLOW CASE - Tihomir Mihalić; Ante Zaninović; Srđan Medić (Journal of Energy Technology, 2025)
The main goal of this study is to investigate the usability of the CFD software ANSYS Student 2023 R1 for students` scientific research. To carry out this investigation, a comparison was carried out of the analytically calculated flow rates through a standard venturi tube with the results obtained by simulations of the flow in the specified program. Given that it is a student, free version of the program, which comes with certain limitations, proving its usability by performing verification and validation on known geometry would be of great benefit. To ensure comparability, a 3D model of the venturi tube was created in accordance with the ISO 5167 Standard. The flow rate was calculated on that selected geometry of the venturi tube, using the well-known equations of fluid mechanics. The selected geometry of the venturi tube was discretised in the ANSYS Student 2023 program, respecting all CFD rules. Comparison of these two sets of results showed a match within 5%.